Offline–Digital Preparedness Strategy for Improving the Quality of Islamic Religious Education (PAI) Learning in Madrasahs - Aulia Safitri; Risfa Tri Ulfa (STAI Al-Mas'udiyah, 2025)
This study aims to analyze the Offline–Digital Preparedness strategy in improving the quality of Islamic Religious Education (PAI) learning in madrasahs with limited infrastructure. A qualitative case study was conducted at MTs Jauhratul Islamiyah, involving the madrasah principal, PAI teachers, and a digital media management team as informants. Data were collected through participatory observation, in-depth interviews, and documentation. The findings suggest that the integration of digital media through structured stages of planning (content curation), implementation (interactive multimedia), and evaluation (gamification) supports students’ engagement, focus, and understanding. The study indicates that the effectiveness of learning is shaped more by teachers’ adaptive pedagogical strategies than by the availability of technology. This study contributes by proposing the Offline–Digital Preparedness strategy as an adaptive pedagogical framework that integrates digital media with offline learning readiness in resource-constrained contexts. However, as this study is limited to a single case and relies on qualitative data, the findings are context-specific and do not provide measurable evidence of learning outcomes. Future research is recommended to expand the context and employ mixed-method approaches to further examine the effectiveness of this strategy.